Culture Shock Dan Adaptasi Studi Fenomenologi Pada Peserta Program Pertukaran Mahasiswa Merdeka Batch 3 Di Universitas Pendidikan Ganesha - Aldi Aldi; Suhardiman Suhardiman; Ahmad Nurul Ihsan (Departement of Mathematics Education, 2024)
This research aims to gain a deeper understanding of the experience of culture shock and adaptation experienced by participants in the Merdek Batch 3 Student Exchange Program at Ganesha University of Education. The method used in this research is a phenomenological approach, which provides space for participants to describe their experiences in depth and subjectively. Data was collected through in-depth interviews with exchange program participants, which were then analyzed using a phenomenological approach. The results of this research show that exchange program participants experience various stages in their adaptation process, starting from the initial culture shock to finally being able to adapt to the new environment. In addition, this research also identifies factors that influence the participants' adaptation process, such as differences in language, system education, cultural values, and social differences. These findings provide valuable insight for universities and other educational institutions in providing effective support for student exchange program participants. This research is expected to provide a better understanding of the culture shock experience and adaptation of student exchange program participants, as well as provide recommendations for educational institutions to improve their exchange programs.